2014
DOI: 10.1016/j.arthro.2014.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Repair of Traumatic Isolated Subscapularis Tendon Lesions (Lafosse Type III or IV): A Prospective Magnetic Resonance Imaging–Controlled Case Series With 1 Year of Follow-Up

Abstract: PURPOSE The purpose of this study was to prospectively assess the efficacy of arthroscopic repair of isolated high-grade subscapularis (SSC) tendon lesions by means of clinical follow-up combined with magnetic resonance imaging investigations. METHODS Between January 2008 and September 2010, 11 patients (9 men and 2 women; mean age, 45 ± 10 years) with Lafosse type III or IV traumatic isolated SSC tendon lesions underwent arthroscopic repair including tenodesis of the long head of the biceps tendon. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 21 publications
0
25
1
1
Order By: Relevance
“…Rerupture rate is also correlated with the delay between injury and surgery [4]. In post-traumatic SSC tendon tears, early arthroscopic repair (within an average of 3.7 months) leads to good functional results, a decrease in fatty degeneration and improvement of muscle mass on imaging [38]. …”
Section: Pathological Featuresmentioning
confidence: 99%
“…Rerupture rate is also correlated with the delay between injury and surgery [4]. In post-traumatic SSC tendon tears, early arthroscopic repair (within an average of 3.7 months) leads to good functional results, a decrease in fatty degeneration and improvement of muscle mass on imaging [38]. …”
Section: Pathological Featuresmentioning
confidence: 99%
“…Furthermore, previous studies have reported good to excellent functional results with acceptable rates of tendon healing after arthroscopic repair in patients with Lafosse type III and IV isolated SSC or combined AS lesions. 21,33 Nonetheless, to the best of our knowledge, the optimal cutoff values for risk of retear of the repaired SSC in terms of tear dimensions (19-mm retraction and 16-mm superoinferior dimension) have not been previously reported.…”
Section: Discussionmentioning
confidence: 89%
“…3 These findings have been less reliably demonstrated in the SSc muscle. The majority of studies have found no progression of fatty infiltration after repair of SSc tendon 5,6,25 ; however, Grueninger et al 20,21 demonstrated significant improvements in SSc muscle fatty infiltration. After SSc tendon repair, higher retear rates have been correlated with higher grades of fatty infiltration 15,27,33 and, in some cases, larger tears.…”
Section: Discussionmentioning
confidence: 99%